Association of Seropositivity and Mortality in Rheumatoid Arthritis and the Impact of Treatment With Disease‐Modifying Antirheumatic Drugs: Results From a Real‐World Study. Issue 2 (13th January 2020) - Alemao, Evo; Bao, Ying; Weinblatt, Michael E.; Shadick, Nancy
Abstract : Objective: Seropositivity for anti–citrullinated protein antibody (ACPA)/rheumatoid factor (RF) in rheumatoid arthritis (RA) is associated with increased overall mortality; however, the association between antibody titers and mortality is not well established. Investigating relationships between antibody titers and mortality may clarify their role in RA pathogenesis. This study was undertaken to evaluate the association of antibody titers with mortality and its modification by disease‐modifying antirheumatic drugs (DMARDs). Methods: Eligible patients with established RA were identified through administrative claims data linked to laboratory results (2005–2016). Patients were categorized by positivity status for ACPA, RF, or both. Patients were further divided into groups by autoantibody titers. DMARD‐exposed patients were categorized into biologic DMARD (bDMARD) and conventional DMARD (cDMARD) subcohorts. Crude mortality rates/1, 000 patient‐years and Kaplan‐Meier curves were compared between antibody categories. Adjusted Cox proportional hazards regression and sensitivity (propensity‐matched patients) analyses were conducted. Results: Overall, 53, 849 and 79, 926 patients had evaluable ACPA and RF status, respectively. For both autoantibodies, mortality rates were significantly higher in seropositive versus seronegative patients (risk increase of 48.0% and 44.0% in ACPA‐ and RF‐positive patients, respectively; P < 0.001 each). Mortality rates were greatest in patients with higher versus lower autoantibody titers (ACPA hazard ratio [HR] 1.60 [95% confidence interval (95% CI]) 1.45–1.76]; RF HR 1.78 [95% CI 1.66–1.91]). In cDMARD‐exposed patients, HRs were higher in seropositive versus seronegative cohorts; in bDMARD‐exposed patients, there was no difference in mortality by serostatus. Conclusion: Elevated ACPA/RF titers were independently associated with increased mortality among patients with RA and persisted in patients treated with cDMARDs but not with bDMARDs.